Case Report: Response to Immunotherapy, Can Radiotherapy Be a Troublemaker? - Martin-Romano, Patricia; Adam, Julien; Scoazec, Jean-Yves; Gouy, Sébastien; Levy, Antonin; Baldini, Capucine; Champiat, Stéphane; Soria, Jean-Charles; Massard, Christophe; Marabelle, Aurélien; Deutsch, Eric; Hollebecque, Antoine (Frontiers in Immunology, 2021)
Immunotherapy has dramatically changed the treatment landscape for several tumor types. However, the impact of previous radiotherapy (RT) on response to immunotherapy is still unknown. We report the case of a 58 years old female diagnosed with a squamous anal cell carcinoma previously treated with RT and having a dissociated response to anti-PD1 agent. An extensive analysis of the immune contexture performed on the tissue collected from both previously RT-treated and untreated lesion highlighted the potential impact of radiotherapy on the immune response.